Formation processes at a high resolution Middle Paleolithic site: Cueva Antón (Murcia, Spain) - Angelucci, Diego E. (2018)
Cueva Antón is a Middle Paleolithic rockshelter located in the valley of the River Mula (Murcia, Spain). The archeological investigation of the site, which began with salvage work in 1991, resumed in 2006 and is still ongoing, uncovered a succession spanning most of MIS 3 and MIS 4 (ca. 75e36 ka) and featuring a well preserved human occupation record. This paper presents the first information about site stratigraphy and site formation processes. Geoarcheological data collected in the field and through micromorphological observation show that the archeological succession at Cueva Antón is mainly composed of alluvial sediments, with thin intercalations of gravitational and slope material. The sedimentary characteristics of the alluvial succession are well preserved as the result of a rapid accumulation rate and the protective effect of the rockshelter. Several sedimentary facies produced by the shifting of distinct fluvial sub-environments (channel, bar and floodplain) are recognized. With the exception of a few units (II-u, a thin buried alluvial soil, and the archeologically richest units at the base of the succession), postdepositional modification is rare. The site was occupied within a framework of infrequent, short-term visits, resulting in a relatively low overall density of finds and the formation of well-defined archeological lenses that correspond to synchronous paleosurfaces preserving the spatial distribution of finds and features. This pattern explains the limited anthropogenic evidence observed in thin sections, even those from units where archeological excavation uncovered significant remains of human occupation.